Analysis of predictive factors associated with pharingocutaneous fistulas after total laryngectomy (Revista Argentina de Cirugía, 2021)
Background: Pharyngocutaneous fistula is the most common complication after total laryngectomy. The factors associated with its development have been studied by several authors without conclusive results.Objective: To evaluate the causes for the development of PCF and to describe the risk factors associated with PCF in the population studied.Material and methods: We conducted a retrospective and observational study with statistical analysis of the variables. A total of 55 patients undergoing initial or salvage total laryngectomy from January 2000 to December 2019 were included. Male-to-female ratio was 48/7. Mean age was 61.3 years. The pathological diagnosis was epidermoid carcinoma in 96.36% of the cases.Statistical analysis: (chi square test and Mann-Whitney test) of the variables related with the development of pharyngocutaneous fistula.Results: The incidence of fistula in patients with laryngectomy was 20%. Spontaneous closure occurred in 72.73% and 3 patients (27.27%) required the use of flaps. In patients with fistula, 63.64% had previous radiotherapy. In these patients, the use of nasogastric tube feeding lasted > 15 days. Mean length of hospital stay in patients with fistula with 23 days.Conclusion: In our environment, previous radiotherapy was the most significant factor associated with the development of fistula. In these patients, fistula took longer to close and required more complex reconstructions in some cases.
Keywords: pharyngocutaneous fistula; predisposing factors; associated variables; pharyngostoma; total laryngectomy